Servant Leadership And Life Satisfaction: The Mediating Role Of Life Goals And Psychological Needs - Liaqat, Hamza; Ullah, Farman; Gul, Rehman (Journal of Business & Tourism, 2022)
The objective of this study is to conceptualizethe proposed research framework of the private schools of Pakistan. The primary objective of this research is to test the relationship between servant leadership and life satisfaction with mediating effect of life goals and psychological needs. This study proposed two mediation effects of life goals and psychological needs between servant leadership and life satisfaction. The study has been tested using data collected from 254 respondents of private schools’ teaching and administrative staff. The results of the study acknowledge that servant leadership negatively affects life satisfaction. Furthermore, the results acknowledge the significantmediation effect between servant leadership and life satisfaction. The results of the study will help private school leadership to improve leadership practices and give a better understanding of what an employee ultimately wants to achieve and how organizations and leaders will help in these phenomena.